Clinical research analysis based on prostate cancer screening diagnosis. (11th January 2022) - Shan, Jiahao; Geng, Xinyu; Liu, Ziyang; Lu, Youlu; Zhou, Raorao; Zhang, Zhengyuan; Xu, Haoran; Zhou, Xiaojie; Ma, Wenzhuo; Zhu, Hengyu; Shi, Hongbin
Abstract: This study aimed to analyse the clinical characteristics and risk factors of patients with positive prostate biopsy at 4–20 ng/mL of prostate‐specific antigen (PSA), construct a new parameter based on this characteristics and assess its diagnostic value for prostate cancer (PCa). Logistic regression analysis was used to clarify the risk factors of PCa, and a new parameter based on the results was constructed. Compare the diagnostic value of various diagnostic parameters for PCa. Logistic multivariate regression analysis revealed that age (OR, 5.269; 95%CI, 2.762–10.050), comorbid diabetes (OR, 2.437; 95%CI, 1.162–5.111), PSA (OR, 2.462; 95%CI, 1.198–5.059) and prostate volume (PV) (OR, 0.227; 95%CI, 0.100–0.516) are risk factors for PCa. The age, PSA and PV of patients were combined to construct a new parameter, that is A‐PSAD = (age × total PSA [TPSA])/PV]. The area under the receiver‐operating characteristic curve(AUC) of A‐PSAD (0.728) for PCa diagnosis was higher than the AUCs of TPSA (0.581), free prostate‐specific antigen (0.514), (F/T)PSA (0.535) and PSAD (0.696), with significant differences. Age, history of diabetes, TPSA and PV are risk factors for PCa(PSA:4‐20ng/mL); in addition, A‐PSAD has a moderate diagnostic value for PCa and may become a new indicator for PCa screening.